PERANAN KOMITMEN ORGANISASI SEBAGAI MEDIASI TERHADAP EFEK ETIKA PERUSAHAAN KEPADA PERILAKU KEWARGAAN ORGANISASI Studi pada PT. Bank Aceh Syariah - Mahdani Ibrahim; Saed Armia; T. Fadhilatul Amri (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2018)
This research was conducted at Bank Aceh Syariah in Tapak Tuan with unit of analysis is employee. Research takes the area of human resource management and organization. The research aims to analyze the role of organizational commitment as a mediation variable to the effect of company ethics and OCB, also analyze the direct influence between variables. The sample was taken with census method as many as 75 employees, the primary data was obtained by circulating the questionnaire. Data analysis using path analysis. The results showed that there is a role of mediation variable of 14.38%, the direct effect between corporate ethics to OCB of 40.5%. The role of organizational commitment variable is significant at level 0,000 and far ˂ 0.005. The effects of the variables tested and the theoretical and managerial implications are discussed in the discussion.